Analysis of the Implementation of the Mudharabah Contract in Idulfitri Savings at Islamic Financial Institutions - M. Finanda Prayoga; Yunus Zamroji (International Journal of Multidisciplinary Research of Higher Education, 2026)
This study aims to analyze the implementation of the mudharabah contract in Idulfitri savings products offered by Islamic financial institutions. The analysis covers the conformity with sharia principles, operational practices, transparency in fund management, and the level of customer understanding. The research employs a qualitative approach with a case study design. Data collection techniques include in-depth interviews, participant observation, and documentation studies with informants consisting of managers, product administrators, sharia supervisory board members, staff, and customers. Data analysis uses the interactive model of Miles and Huberman through the stages of reduction, presentation, and conclusion drawing. Data validity is examined through source and technique triangulation. The findings reveal the existence of a hybrid mudharabah practice characterized by stabilized profit-sharing, the predominance of consumptive-religious motives among customers, and an asymmetry of understanding between managers and customers. These conditions reflect an adaptation between sharia principles and the practical needs of society. The contribution of this study is the development of an integrative evaluation model based on transparency, Islamic financial literacy, and strengthened institutional communication to enhance the effectiveness of sharia financial practices at the micro level.